Social responses to expressive suppression The role of personality judgments. [article]. - Tackman, Allison M.
Why do people who suppress their emotion-expressive behavior have difficulty forming close, supportive relationships? Previous studies have found that suppression disrupts the dynamics of social interactions and existing relationships. We evaluated a complementary hypothesis: that suppression functions as a behavioral cue leading others to form negative personality impressions of suppressors, even at zero-acquaintance. In 2 studies, participants reported personality judgments and other impressions of targets who either suppressed or expressed their emotion-expressive behavior in response to amusing or sad film clips. In findings replicated across studies, targets who suppressed either amusement or sadness were judged as less extraverted, less agreeable, and more interpersonally avoidant and anxious than targets who expressed emotions, and participants were less interested in affiliating with suppressors compared with expressers. Effects were amplified when targets suppressed amusement (compared with sadness) and when participants knew the emotional context (compared with when they did not) and, thus, could form expectations about what emotions targets should be showing. Extraversion and agreeableness judgments mediated the effect of suppression on participants' disinterest in affiliating. In Study 2, which extended Study 1 in several ways, effects were pronounced for the enthusiasm aspect of extraversion and the compassion aspect of agreeableness. We also found evidence that judgments of suppressors do not simply fall between neutral and fully expressing targets; rather, judgments of suppressors are qualitatively different. We discuss implications for understanding the social consequences of emotion regulation-in particular, how beyond disrupting relationships, suppression may prevent some relationships from even forming in the first place. -- (from the authors)